The Influence of Manpower, Information Technology and Intellectual Property Rights on Creative Economy Growth in Java Island - Insana, Dwi Rorin Mauludin; Yolanda, Yolanda; Susilastuti, Darwati (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The era of the industrial revolution 4.0 was marked by the development of the information economy era accompanied by the proliferation of new discoveries in the fields of technology, information, and communication. In this era, the creative economy is growing. In addition to the use of information technology, the creative economy prioritizes workers who have ideas and creativity, so the protection of intellectual property rights is very important in the growth and development of the creative economy. The purpose of this study is to identify, study, analyze, find and describe the influence of labor, information technology and intellectual property rights on creative economic growth in Java. This study uses secondary data in the form of panel data consisting of 6 provinces in Java for the period 2010-2019. Data analysis used panel data regression. The results of data analysis show that partially or simultaneously labor, information technology and intellectual property rights have a positive and significant influence on the growth of the creative economy in Java. The results of this study are expected to be input for the provincial government in Java to better support and assist creative economy actors to obtain legal protection for intellectual property rights and play a more active role in increasing the quantity and quality of creative and innovative human resources as well as mastering information technology and infrastructure provision. more adequate information technology for the development of the creative economy.